To apply the Distributive Property to the expression \((2x - 2)(x - 6)\), you need to distribute each term in the first expression by each term in the second expression.
Here's how it's done step-by-step:
-
Distribute \(2x\) to both \(x\) and \(-6\): \[ 2x \cdot x = 2x^2 \] \[ 2x \cdot (-6) = -12x \]
-
Distribute \(-2\) to both \(x\) and \(-6\): \[ -2 \cdot x = -2x \] \[ -2 \cdot (-6) = 12 \]
-
Now, combine all the like terms: \[ 2x^2 - 12x - 2x + 12 = 2x^2 - 14x + 12 \]
So, the expression \((2x - 2)(x - 6)\) rewritten using the Distributive Property is
\(2x^2 - 14x + 12\).
Thus, the correct response is: 2x² − 14x + 12.